Schiff Bases Derived from 2‐Amino‐6‐methylbenzothiazole, 2‐Amino‐5‐chloropyridine and 4‐Chlorobenzaldehyde: Structure, Computational Studies and Evaluation of Biological Activity. Issue 38 (10th October 2022) - Hanif, Muhammad; Kosar, Naveen; Mahmood, Tariq; Muhammad, Mian; Ullah, Farhat; Tahir, Muhammad Nawaz; Ribeiro, Alany Ingrid; Khan, Ezzat
Abstract: Molecular structure of (E)‐ N ‐(4‐chlorobenzylidene)‐6‐methylbenzo[ d ]thiazol‐2‐amine, (E)‐ N ‐(4‐chlorobenzylidene)‐5‐chloropyridin‐2‐amine was determined in solution and solid states by various techniques such as UV/Vis, FT‐IR, NMR spectroscopy, HRMS and X‐ray diffraction. Both the Schiff base compounds crystallize as monoclinic system with identical space group P21 /c. Supramolecular interactions observed in X‐ray structure are validated via density functional theory (DFT) calculations. Further, the reactivities of both compounds (ligands) are analysed with the help of frontier molecular orbitals (FMOs) analysis. They were treated with Cu and Ag salts to obtain corresponding coordination complexes. Both the ligands contain three possible coordination sites namely, endocyclic nitrogen, sulfur and the imine nitrogen. Among these nucleophilic centres, imine nitrogen is more basic and readily coordinates with Cu and Ag metals. The compounds were tested for their fluorescence properties and all the compounds were found to be fluorescence active. The Schiff base ligands and their complexes were also tested for preliminary biological activities such as antibacterial, antioxidant and enzyme inhibition. Molecular docking studies were implemented to compare and validate the enzyme inhibition potentials of ligands. Moderate activities were observed for all compounds. The activities of ligands enhanced by complexation with Cu(II) and Ag(I) metals ions. Abstract : Molecular structure of (E)‐ N ‐(4‐chlorobenzylidene)‐6‐methylbenzo[ d ]thiazol‐2‐amine, (E)‐ N ‐(4‐chlorobenzylidene)‐5‐chloropyridin‐2‐amine was determined in solution and solid states. Both the Schiff bases 1 and 2 crystallize as monoclinic system with identical space group P21 /c. They were treated with Cu and Ag salts to obtain corresponding coordination complexes. Compounds were tested for their fluorescence, antibacterial, antioxidant and enzyme inhibition properties.